On the Functional Resynthesis of Thromboplastin (“TP”) from its Fractions and Various Substitutes - Hecht, E; Wijngaabjds, G (Thrombosis and Haemostasis, 1969)
Recombination of the low active lipid fraction with the inactive non-lipid fraction of brain thromboplastin has been proved to be just as successful in restoring the original high thromboplastic activity as the recombination of the corresponding material obtained from lung thromboplastin.The properties of the individual components, of thromboplastin, its fractions obtained by different ways, and of their substitutes were studied comparatively; the influence of the solvents used was also investigated.Experiences obtained were collected to prepare a high active and stable brain thromboplastin.Only the lipid- and non-lipid fraction obtained by pyridin is successful in regenerating the original thromboplastic activity, in contrast with the reunion of both fractions produced by Sephadex G-25, Sephadex LH-20 and butanol.The lipid fraction can be fully replaced by the lipid activator, PE from soy-beans and partly by synthetic dioleoyl PE, however this is not possible with natural and synthetic PC and lyso PC.The results of experiments to replace the non-lipid fraction by various amino acids, peptides or proteins were poor.A full regeneration of the thromboplastic activity with the suspended fractions is only successful after a previous solution of the components in pyridin or chloroform and evaporation.The rebuilt of the original thromboplastic activity was complete only as long as contaminated non-lipid fractions were used. Non-lipid fractions, quantitatively free of lipids, were ineffective.